1993
DOI: 10.1111/1540-5850.00977
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Capital Budgeting: An Examination

Abstract: The state of capital budgeting theory is going through its growing pains. While traditional literature on capital budgeting is grounded in rational decision‐making, Nunn (1990) has suggested that such an approach is too limited to be of significant value. New theories, he argues, need to reflect differences in capital demand and differences in approaches to local policy, thereby reflecting both the economically‐rational and other components of capital budgeting. In this study, we examine the rigor of the tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 0 publications
0
22
1
Order By: Relevance
“…Similar to the lagged investment in infrastructure, the academic research on capital investment is also surprisingly limited in both theoretical foundation and empirical evidence. Forrester wrote in the middle of 1990s that “the theoretical basis for capital budgeting is thin and there is little empirical or other rigorous research on capital budgeting” (Forrester , p.87). The lack of scholarly attention continued and there has been relatively little academic inquiry on this topic in recent decades (Fisher and Wassmer ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the lagged investment in infrastructure, the academic research on capital investment is also surprisingly limited in both theoretical foundation and empirical evidence. Forrester wrote in the middle of 1990s that “the theoretical basis for capital budgeting is thin and there is little empirical or other rigorous research on capital budgeting” (Forrester , p.87). The lack of scholarly attention continued and there has been relatively little academic inquiry on this topic in recent decades (Fisher and Wassmer ).…”
Section: Introductionmentioning
confidence: 99%
“…Capital planning is conducted through the CIP; projects in the first year of the CIP are included in the capital budget. Subnational governments that have a CIP tend to have a separate capital budget, given that appropriations for capital projects require special analysis and approval from voters (Forrester ; Mikesell ; Sekwat ) . Mikesell () asserts that half of the state governments have a separate executive capital budget that is passed in legislative processes, while the other states insert their capital project requests as items in the operational budget.…”
Section: Introductionmentioning
confidence: 99%
“…Sekwat () and Forrester () found that most cities who implemented long‐range capital planning also adopt a separate capital budget.…”
mentioning
confidence: 99%
“…Capital budgeting is an essential and important component of the municipal budgeting and planning processes. Traditionally, the literature on capital budgeting has been focused on rational decision-making (Forrester, 1993). However, in the last twenty to thirty years new theories have emerged to reflect the differences in capital demand and approaches to local policy (Nunn, 1990).…”
Section: Municipal Sustainabilitv Checklists For Developmentmentioning
confidence: 99%
“…Such criteria may not be useful or appropriate to governments as it is limited by the fact that the analyses do not reflect the possibilities of failure (McKenna, 1980), an unequal distribution of actuarial benefits over time (Neenan, 1981 ), an understatement of the opportunity cost of capital (Snyder, 1977) and other constraints such as management priorities and legal obligations (Millar, 1988). Historically, the literature and theoretical evidence for capital budgeting has been weak with little empirical evidence (Forrester, 1993). While there has been some longitudinal and crosssectional analyses, the research has been constrained by methodological limitations and small sample sizes (Millar, 1988), as well as measurement inconsistencies (Kamensky, 1984;Pagano, 1984;Huq, Taylor and Whritenour, 1986;Millar, 1988).…”
Section: Municipal Sustainabilitv Checklists For Developmentmentioning
confidence: 99%